Pendekatan Inovatif dalam Pembelajaran IPA : Sebuah Systematic Review 2020-2025 - Amanda Gosynda Putri; Ernita Vika Aulia; Muhamad Arif Mahdiannur (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Natural Science (IPA) learning is an important foundation in developing students' scientific literacy, critical thinking skills, and scientific attitudes. However, the learning process still faces many challenges related to low learning interest, the dominance of conventional methods, and limited use of technology. This article aims to analyze the effectiveness of innovative approaches in science learning through a systematic review of 25 national and international journal articles published in 2020–2025. The systematic review method was carried out through the stages of identification, selection, data extraction, and thematic analysis. The results of the analysis show that the Problem-Based Learning (PBL), Inquiry-Based Learning (IBL), STEM Learning, and digital technology integration (PhET Simulation, mobile learning, gamification, blended learning) approaches have been proven to have a positive impact on learning outcomes, critical thinking skills, creativity, and student motivation. The thematic analysis resulted in four main themes: (1) strengthening critical thinking skills through PBL, (2) developing creativity and scientific literacy through IBL, (3) STEM integration to improve collaboration and scientific attitudes, and (4) utilizing digital technology for motivation and understanding abstract concepts. This study concludes that a combination of various innovative approaches is needed to make science learning more relevant to the demands of the 21st century.